2023
DOI: 10.3389/fpsyt.2023.1080681
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in young adults with autism and ADHD: An event related potentials study

Abstract: BackgroundAtypicalities in perception and interpretation of faces and emotional facial expressions have been reported in both autism and attention-deficit/hyperactivity disorder (ADHD) during childhood and adulthood. Investigation of face processing during young adulthood (18 to 25 years), a transition period to full-fledged adulthood, could provide important information on the adult outcomes of autism and ADHD.MethodsIn this study, we investigated event-related potentials (ERPs) related to visual face process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…Larger N170 indicates greater neural activity in encoding facial configuration, suggesting greater brain flexibility in processing facial structural information and representing better facial configuration encoding ability (Yang et al, 2020 ). Since emotion face recognition paradigms have been mostly conducted in special participant groups, the smaller N170 amplitudes elicited by patients with severe depression, ADHD, and schizophrenia compared to normal controls also indirectly concur with our experimental results (Aydin et al, 2023 ; Chen et al, 2022 ; Salisbury et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…Larger N170 indicates greater neural activity in encoding facial configuration, suggesting greater brain flexibility in processing facial structural information and representing better facial configuration encoding ability (Yang et al, 2020 ). Since emotion face recognition paradigms have been mostly conducted in special participant groups, the smaller N170 amplitudes elicited by patients with severe depression, ADHD, and schizophrenia compared to normal controls also indirectly concur with our experimental results (Aydin et al, 2023 ; Chen et al, 2022 ; Salisbury et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…Given the role of impaired face emotional recognition as a core feature in autism, our results have potential clinical significance. Prior studies have already supported the notion that classical N170 latencies could be an indicator of autism [e.g., Aydin et al, 2023 ]. Moreover, Mason et al (2022) provided results which emphasize the classical N170 component as a promising stratification marker in clinical trials, since N170 latencies have been associated to social difficulties from childhood to adolescence.…”
Section: Discussionmentioning
confidence: 96%
“…The paradigm employed here increases ecological validity and allows for a more naturalistic social cognition approach, which can further elucidate the role of the face sensitive N170 in autism. Studies have shown delayed N170 latencies in individuals with autism, reflecting less efficient face processing or incomplete developmental maturation ( Kala et al, 2021 ; Aydin et al, 2023 ; Farashi et al, 2023 ). Moreover, the right hemisphere N170 latency to upright faces was accepted into FDA Center for Drug Evaluation and Research (CDER) Biomarker Qualification Program ( Webb et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One area of interest in this field is the study of event-related potentials (ERPs). Notably, the N170 is an ERP component and a well-established marker of face processing that has been found to be abnormal in individuals with ASD [ 11 , 12 , 13 , 14 , 15 ]. Accordingly, the N170 component has shown promise as a potential biomarker for assessing face-processing abilities in individuals with ASD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%